2009
DOI: 10.4315/0362-028x-72.6.1279
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Salmonella in Vegetables from Mexico

Abstract: The present study is an overview of the role of vegetables as a transmission vehicle of Salmonella in Mexico. One hundred samples of each of 17 different vegetables were analyzed during a period of 18 months. Salmonella was isolated from 98 samples. Salmonella enterica serovar Typhimurium was isolated from the highest percentage of samples with typeable Salmonella isolates (23.9%), followed by S. enterica subsp. arizonae and Salmonella Choleraesuis each from 16.9%, Salmonella Gallinarum from 11.1%, Salmonella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 13 publications
7
66
2
3
Order By: Relevance
“…Different studies have shown very high prevalence rate of Salmonella contamination of vegetables [8,14] and different animal products [6,21,22]. The prevalence rates from these studies compares favorably with the 20% of the 120 study samples and the 96% of the 25 pure Salmonella isolates of DNA-PCR Salmonella invA gene detectable results obtained in this current study.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Different studies have shown very high prevalence rate of Salmonella contamination of vegetables [8,14] and different animal products [6,21,22]. The prevalence rates from these studies compares favorably with the 20% of the 120 study samples and the 96% of the 25 pure Salmonella isolates of DNA-PCR Salmonella invA gene detectable results obtained in this current study.…”
Section: Discussionsupporting
confidence: 76%
“…Some studies in Nigeria [8,9,10] and at different parts of the world [11,12,13,14] have indicated the pollution and or contamination of most common vegetables by Salmonella species. In North-Central Nigeria where the occupation is predominantly farming, most small scale farmers cultivate vegetable farms; and the produce from these farms are generally marketed at the different markets within the respective local communities.…”
Section: La Detection Moleculaire Des Especes De Salmonelles De Legummentioning
confidence: 99%
“…and pathogenic Escherichia coli strains, so its application on agricultural field without prior treatment, such as proper composting, poses health risks due to the potential contamination of the primary production environment (soil, irrigation water and cultivated vegetables) with these pathogens. According to the World Health Organization (WHO), the five keys practices to grow safe fruits and vegetables are: (1) Practice good personal hygiene; (2) Protect fields from animal faecal contamination; (3) Use treated faecal waste; (4) Evaluate and manage risks from irrigation water; (5) Keep harvest and storage equipment clean and dry [42]. Food safety has to be integrated along the entire food chain from farm to table, with the government (preferably one single food safety agency), industry and consumers sharing the responsibility [43].…”
Section: Resultsmentioning
confidence: 99%
“…Surveys on the type and concentrations of pathogens on vegetables and their survival under natural field conditions are still scarce, although increasing (38). The reported level of human pathogens in produce seems to vary considerably, e.g., between regions (3,32,41,50). It is uncertain as to what extent pathogens present in the soil can become internalized into the plant through the root system or be transferred to leaf surfaces through rain splash, with possible internalization via leaf orifices, but both transmission routes constitute potential food safety risks for consumers (6,16,37,46).…”
mentioning
confidence: 99%